Dietary fulvic acid increased growth, stress tolerance and disease resistance against Vibrio harveyi in Asian seabass (Lates calcarifer) juvenile - Fazel Zoheiri; Seyed Hossein Hoseinifar; Mansour Torfi Mozanzadeh; Mina Ahangarzadeh; Thora Lieke; Hien Van Doan (Aquaculture Reports, 2023)
An 8-week husbandry trial was carried out toexamine the impacts of graded levels of dietary fulvic acid (FA) on growth, stress, and disease resistance of Asian seabass (Lates calcarifer, 38.2 g) juveniles. Five levels of FA were included in a basal diet (470 g kg-1 crude protein, 150 g kg-1 crude lipid) to prepare experimental diets, including: 0 (control), 2.5, 5.0, 10, and 15 g kg-1 diet. Two hundred and twenty-five fish (38.2 ± 0.1 g) were stocked randomly into 15 1000-L circular polyethylene tanks (15 fish tank-1) filled with 800 L disinfected seawater and fed with the experimental feeds three times daily. Each dietary treatment had three replicates. Tanks were supplied with seawater (32.2 °C, 45.0 ppt) in a flow-throw system. At the end of the husbandry trial, fish were challenged with Vibrio harveyi and air exposure stress for one min. Fish fed FA-supplemented diets showed a positive quadratic growth response, and those fed with a 5 g FA kg-1 diet had higher final weight and weight gain percentage than the control. Feed intake in fish fed FA-supplemented diets were higher than in control, showing significant linear and quadratic trends (P < 0.05). The highest and lowest skin mucus lysozyme (LYZ) and serum alternative complement pathway (ACH50) activities were in fish fed 10 and 15 g FA kg-1 diets, respectively, exhibiting a quadratic response to dietary FA. Serum total protein level (TP) in fish fed FA-supplemented diets was higher than in the control group. Medium or high levels (10–15 g kg-1) of FA significantly enhanced the survival rate against Vibrio harveyi, which was associated with increased activities of serum lysozyme and ACH50 as well as liver glutathione peroxidase activity in these groups. Air exposure induced oxidative stress in all treatments and gradually reduced antioxidant enzyme activities associated with increased malondialdehyde content in the liver. Furthermore, air exposure suppressed some immune responses, including serum total immunoglobulin and TP levels. Still, LYZ activity was restored after 24 h, with the highest level found in fish fed 5 g FA kg-1 diet. Based on the broken-line regression analysis, the adequate level of FA in the diet for Asian seabass is 4.4 g kg-1.